The logic of appropriability: From Schumpeter to Arrow to Teece - Sidney G. Winter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
This note expounds the abstract fundamentals of the appropriability problem, re-assessing insights from three classic contributions those of Schumpeter, Arrow and Teece. Whereas the first two contributions were explicitly concerned with the implications of appropriability for society at large, Teece's main concern was with practical questions of business strategy and economic organization. This note argues that, his practical concerns notwithstanding, Teece contributed, en passant but fundamentally, to the clarification of basic questions that previous authors had addressed less comprehensively and less satisfactorily. Specifically, his analysis of the innovator's access to complementary assets, undertaken from a contracting perspective, can be seen as filling a significant gap in the previous theoretical discussion of appropriability.
Keywords: 330; appropriability; innovation; complementary assets; patents; intellectual property; Innovation; Immaterialgüterrechte; Patent; Dogmengeschichte